Critical Thinking in Academic Reading - Muhamad, Ainon Jariah; Mohd. Asraf, Ratnawati (2008)
The purpose of the study was to examine whether students were able to respond critically to academic texts given. Lack of critical thinking skills in reading, especially at tertiary level, is a great handicap to undergraduates, as they will find it difficult, or even unable, to analyze and evaluate reading materials. What were the critical reading strategies the students employed, and what were their perceptions of reading academic texts in English, were the two research questions addressed in this study. Data were gathered via the think-aloud protocol and the retrospective interview, the questionnaire, and the face-to-face semi-structured interview. These were transcribed, translated, segmented, and coded for analysis. The results of the study revealed that although undergraduates were able to utilize the critical reading strategies, they were only able to do so to a certain extent. It is therefore incumbent upon instructors and policy makers to seriously look into the teaching of critical reading to enhance the quality of education. Students need to be made more aware of the benefits of critical reading, and to acquire critical reading skills, as these skills will undoubtedly help them in tertiary level reading in their quest for knowledge.